2022
DOI: 10.3389/fmed.2022.797153
|View full text |Cite
|
Sign up to set email alerts
|

Health professional student’s volunteering activities during the COVID-19 pandemic: A systematic literature review

Abstract: BackgroundThe Coronavirus Disease 2019 (COVID-19) crisis has forced health and education services to use additional human resources, such as health professional students. Students in the health professions, particularly those in the medical field, can participate in a variety of voluntary activities, both directly and indirectly in health services. The aim of this review was to determine the affecting factors, types of activity, and benefits of undertaking a volunteering role by the health professional student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…In the study conducted by Zhu et al (2022), the COVID-19 risk perception was indicated as a moderating factor between volunteer behavior and empathy. Previous researches on volunteering have demonstrated that perceived risk of COVID-19 or fear of COVID-19 was negatively associated with intention or willingness to volunteer (Al Gharash et al, 2021;Tran et al, 2022;Umar et al, 2022). In fact, during the COVID-19 crisis, the exposure risk to the infection is higher among volunteer medical students due to their lack of clinical experience (Adejimi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the study conducted by Zhu et al (2022), the COVID-19 risk perception was indicated as a moderating factor between volunteer behavior and empathy. Previous researches on volunteering have demonstrated that perceived risk of COVID-19 or fear of COVID-19 was negatively associated with intention or willingness to volunteer (Al Gharash et al, 2021;Tran et al, 2022;Umar et al, 2022). In fact, during the COVID-19 crisis, the exposure risk to the infection is higher among volunteer medical students due to their lack of clinical experience (Adejimi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, Tran et al (2022) found that the health status, self-awareness, the prevalence of chronic diseases and fear level of COVID-19 were related to healthcare students' intention to volunteer. According to Umar et al (2022), the factors that lead someone to refuse to take a volunteer position are the fear of the risk of infection and the identification of his personal identity as a risky person. As best as we know, predictors of volunteer behavior during the COVID-19 pandemic have not been fully explored, including perceived risk of COVID-19.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations